Développer la compétence interculturelle en classe de français langue étrangère à travers le roman noir Derrière les panneaux il y a des hommes de Joseph Incardona - Ráčková , Lucia; Schmitt , François; Zázrivcová , Monika (Neofilolog, 2022)
Current research on interculturality in foreign language teaching focuses on the development of the intercultural personality of the learner based on his social representations. In this context, the introduction of crime fiction in French foreign language teaching makes it possible to take the complexity of the human personality more efficiently into account when developing the intercultural competence of the learner. Based on a thematic analysis of the novel Derrière les panneaux il y a des hommes (Behind the Panels There Are Men) by Joseph Incardona, which aims at highlighting the references to French culture in the text, and from a linear analysis centered on the characters and their complex personalities, the article proposes to apply the cultural and intercultural approaches of language didactics to literature. In this way, in order to develop cultural competence, the learners first learn to identify the cultural clues referring to French society in the text. Then, they learn to adopt a positive attitude of openness towards others through the characters of the novel to develop their intercultural competence.